Phonetic isoglosses in the speech of Circassian repatriates in the Kabardino-Balkarian Republic - Marita M. Abazovа; Zaudin G. Khutezhev (Кавказология)
The article examines phonetic isoglosses in the speech of Circassian repatriates living in the Kabardino-Balkarian Republic in comparison with the literary Kabardino-Circassian language. The study of the speech of Circassian repatriates from Syria and Turkey is of scientific interest not only for linguists but also for historians and ethnographers. It appears that archaic forms of some consonants maintained in the dialects and dialects of the literary Kabardino-Circassian language are seen in the speech of representatives of Circassian repatriates. It is noted that negations are expressed using negative affixes –I/ –k as synonyms, and the statement is a morpheme–c; the process of affrication of palatalized posterior consonants is not yet complete, soft hissing spirants f and w are frequently heard in speech, etc. Some vocalism system anomalies are observed in repatriates’ speech. It is concluded that Circassian repatriates in the Kabardino-Balkarian Republic speak with a variety of phonetic traits.